2018
DOI: 10.24275/uam/izt/dcbi/revmexingquim/2019v18n1/saenz
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICOCHEMICAL, MORPHOLOGICAL AND STRUCTURAL CHARACTERIZATION OF THE CHITIN AND CHITOSAN OF Tenebrio molitor AND Galleria mellonella INSECTS

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Recently, Saenz-Mendoza et al [ 28 ] had also reported similar values, despite that, these researchers established the molecular weight through capilar viscosimetry technique, obtaining an average viscosimetric molecular weight. Chitosan molecular weight differences found may be attributed to different factors such as obtention source, analysis or methods performed for its determination, and de-acetylation treatment conditions (type and reagents concentrations, time, temperature, alkaline steps repetitions, atmospheric pressure, particle size and chitin-solvent relation) [ 9 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Saenz-Mendoza et al [ 28 ] had also reported similar values, despite that, these researchers established the molecular weight through capilar viscosimetry technique, obtaining an average viscosimetric molecular weight. Chitosan molecular weight differences found may be attributed to different factors such as obtention source, analysis or methods performed for its determination, and de-acetylation treatment conditions (type and reagents concentrations, time, temperature, alkaline steps repetitions, atmospheric pressure, particle size and chitin-solvent relation) [ 9 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan films properties are influenced by several factors such as solvent (type and concentration), plasticizer and the presence of co-polymers and additives; nevertheless, chitin source and chitosan properties (molecular weight and deacetylation degree) also affect the physicochemical and microbiological properties of its derived films [ 24 ]. Most of the studies performed in meat products, using chitosan films, have employed commercial chitosans, which are obtained from maritime industry wastes [ 25 ]; since that, current research studies have been oriented to explore the properties of chitin and chitosan obtained from other sources available in nature, such as grasshoppers and other insects [ 25 , 26 ]. In this regard, Monter-Miranda et al [ 27 ] characterized physicochemical, morphological and structurally, chitin and chitosan obtained from Brachystola magna (Girard), a polyphagous insect (grasshopper) which attacks corn and bean crops from the northern part of Mexico, causing large economic losses by reducing the production of these crops, and reported that the chitosan obtained from this insect presents chemical similarities with commercial ones.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a product of the deacetylation of chitin, widely distributed in nature, in shells of crustaceans, insects, 7,[15][16][17][18][19] in nematodes, cephalopod beaks 20 and in fungal cell walls. 7,15,19…”
Section: Introductionmentioning
confidence: 99%
“…
The main control method of these phytopathogens are chemical fungicides. 6,7 In 2018, Mexico ranked 5th in the world in the consumption of fungicides and bactericides with a total of 28,601 tons, followed by insecticides and herbicides. 2 Such as Metam sodium, 5,8 2Thiocyano methyl thiobenzo thiasol, Metalaxil, Tebuconzole, Carbendazim, Azoxystrobin, Propamocarb, as examples.
…”
mentioning
confidence: 99%
“…Therefore, the integrity of the conidium and its quality parameters such as conidial germination, viability and degree of infectivity are main issues to be evaluated together with the conidia production (Miranda-Hernández et al, 2014). An initial and rapid assessment through laboratory bioassay using Tenebrio molitor (Coleoptera: Tenebrionidae), a model insect susceptible to some EF (Sáenz-Mendoza et al, 2019), can be a strategy to evaluate the holistic performance of the conidia related to their production conditions (Rodriguez-Gomez et al, 2009). Initial approaches to increase the conidia production at an industrial level have been the modification of substrates or the culture conditions (Lopez-Perez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%